Indigenous/traditional climate-smart practices effects on soil fertility and maize yield in Mauritius agricultural system - Vagish Ramborun; Sunita Facknath; Bhanooduth Lalljee (Journal of Agriculture and Food Research, 2021)
The study investigated the compounding effects of a climate smart package based upon indigenous/traditional practices implemented by local farmers decades ago. The package comprised combinations of various practices such as mulch, no-tillage, tillage and nitrogen based fertilizer. Their compounding effects were investigated on maize growth, grain yield, and plant biomass in three successive crop cycles in the region of Vacoas, Mauritius. Nitrogen based fertilizer (ammonium sulphate) was applied at 120 kg/ha to its corresponding treatment, and maize mulch was applied as full coverage (24 t/ha). A 4 × 3 × 2 completely randomized block design with 4 treatments: mulch, fertilizer, tillage and no-tillage was tested at 2 levels and replicated 3 times in the trials. Results showed that fertilizer was the most important factor in maize production; maize treated with fertilizer, by itself or in combination with other treatments, gave the highest yield. Tillage was seen to increase bulk density, while mulch was observed to limit loss of soil organic carbon, and potassium. Addition of fertilizer was found to be the cause in reducing pH. The combination of tillage-mulch-fertilizer was expected to be high yielding; however it was observed that potassium was the limiting factor that induced a reduction in overall yield.